Energetické hodnocení bytového domu - Trajer, Štěpán (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Bakalářská práce se zabývá hodnocením hospodárnosti panelového domu. Hodnotícím mechanizmem je zvolen energetický audit, který hodnotí budovu z hlediska energetického, ekonomického a environmentálního. Byly navrhnuty jednotlivé opatření pro zlepšení vlastností budovy. Jednotlivá opatření byla poskládána do dvou variant. A zhodnocena.

This thesis deals with the evaluation panel economical house. The evaluation mechanism is selected, an energy audit that assesses buildings in terms of energy, economic and environmental. Individual measures were designed to improve the properties of the building. Individual measures have been put together in two variants. And evaluation.
Energy assessment of residential building
Keywords: Energetický audit; bytový dům; součinitel prostupu tepla; hodnocení; úsporná opatření; Energy audit; apartment building; heat transfer coefficient; evaluation; austerity measures.